DIGITAL INDIA: A Mega Project of Indian Government to Provide Internet and Connect250,000Villages by2019 - Aneet, (Gyan Management Journal, 2015)
The Digital India Project of the BJP government aims to connect all Gram Panchayats by broadband internet, promote egovernance and transform India into a connected knowledge economy.The government is budgeting an $18 billion (approximately Rs 114,768 crore at current exchange rates) to provide fast internet connections for all, popularizing Prime Minister Narendra Modi's campaign promise to connect 250,000 villages in lndia by 2019. The government's tech push aims to bridge India's digital divide, bringing in large investments in technology manufacturing.So far the progress on the project has been slow since its inception in 2011. "Now we are at a place where we can take off," said the communications and information technology minister Ravi Shankar Prasad. "The idea is to bridge the gap between haves and have-nots of services aIJd deliverables."
Keywords: Digital India; government; BJP; broadband internet